Fort Chipewyan and the Shaping of Canadian History, 1788-1920s: "We like to be free in this country" - Payne, Michael (Labour / Le Travail, 2013)
The article reviews the book, "Fort Chipewyan and the Shaping of Canadian History, 1788-1920s: 'We like to be free in this country,'" by Patricia A. McCormack.
Keywords: Canada; FORT Chipewyan & the Shaping of Canadian History 1788-1920s: We Like to Be Free in This Country (Book); FUR trade; History; MCCORMACK; Patricia A.; Nonfiction